PROSES BERPIKIR KRITIS SISWA SMP BERKEMAMPUAN MATEMATIKA TINGGI DALAM MENYELESAIKAN SISTEM PERSAMAAN LINEAR DUA VARIABEL - Muhammad Ahsanul Amala; Agung Lukito; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the critical thinking process of junior high school students with high mathematical ability in solving a two-variable linear equation system (SPLDV) problem. This study uses a descriptive qualitative approach. The research subject was selected through purposive sampling based on a mathematical ability test, teacher recommendation, and the student's willingness to participate actively. Data were collected through a problem-solving task and a semi-structured interview, then analyzed using the Miles, Huberman, and Saldaña model, covering data condensation, data display, and conclusion drawing. The subject's critical thinking process was analyzed based on Facione's six indicators, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results show that the subject fulfilled the interpretation, analysis, evaluation, and inference indicators well. The subject correctly formulated the mathematical model and corrected a statement that contradicted the given data. However, the subject showed weakness in self-regulation, since verification was limited to repeating the same method without exploring alternative strategies. These findings indicate that high mathematical ability does not always correspond to an equally strong self-regulation ability. Teachers need to train students to verify their answers through varied approaches so that their critical thinking skills develop more comprehensively.